Microbial production and functional assessment of γ-polyglutamic acid isolated from Bacillus sp. M-E6 - Manika, Verma; Devi, Palanisamy Bruntha; Majaw, Jessica; Rani, Potunuru Uma; Reddy, G. Bhanuprakash; Kavitake, Digambar; Shetty, Prathapkumar Halady (Frontiers in Microbiology, 2025)
This study describes the production and functional evaluation of γ-polyglutamic acid (γ-PGA) synthesized by Bacillus sp. M-E6, isolated from a traditional fermented food. Among 103 isolates screened, strain Bacillus sp. M-E6 exhibited the highest γ-PGA yield (4.9 g/L) and was taxonomically identified through 16S rRNA gene sequencing. The γ-PGA was extracted and characterized for the physicochemical and techno-functional properties. The γ-PGA was purified using ion-exchange column chromatography, and its molecular mass was determined by Electrospray Ionization-Mass Spectrometry (ESI-MS), which found it to be 60.42 kDa. Fourier-transform infrared spectroscopy and nuclear magnetic resonance analysis confirmed the polymer’s structure as γ-PGA. Thermogravimetric analysis revealed high thermal stability (>600 °C), while scanning electron microscopy showed a porous and granular morphology. The γ-PGA showed potent functional properties such as water holding capacity (196.21%), water solubility index (96.64%), water contact angle (26°), oil binding capacity (104.78%), flocculation activity (29.32%), emulsifying activity (79.33%), and antioxidant activity. Further, the γ-PGA showed an excellent cryoprotectant activity with probiotic bacteria Lacticaseibacillus rhamnosus (97.57%), Streptococcus thermophilus (93.47%), and Limosilactobacillus fermentum (84.53%) as evaluated by flow cytometric analysis and direct plate count. These findings highlight the multifunctional potential of γ-PGA from Bacillus sp. M-E6 as a natural, biocompatible cryoprotectant with promising applications in the food, cosmetic, and biomedical industries.